Mid-term and long-term follow-up of intracranial aneurysms treated by the p64 Flow Modulation Device: a multicenter experience. (20th July 2016) - Briganti, Francesco; Leone, Giuseppe; Ugga, Lorenzo; Marseglia, Mariano; Macera, Antonio; Manto, Andrea; Delehaye, Luigi; Resta, Maurizio; Resta, Mariachiara; Burdi, Nicola; Nuzzi, Nunzio Paolo; Divenuto, Ignazio; et al.
Abstract : Background: Experience with the endovascular treatment of cerebral aneurysms using the p64 Flow Modulation Device is still limited. This study discusses the results and complications of this new flow diverter device. Methods: 40 patients (30 women, 10 men) with 50 cerebral aneurysms treated in six Italian neurointerventional centers with the p64 Flow Modulation Device between April 2013 and September 2015 were retrospectively reviewed. Results: Complete occlusion was obtained in 44/50 aneurysms (88%) and partial occlusion in 3 (6%). In the other three aneurysms (6%), two cases of asymptomatic in-stent thrombosis and one intraprocedural occlusion of the parent vessel occurred. Technical complications were observed in eight procedures (16%). Permanent morbidity due to acute in-stent thrombosis and consequent ischemic stroke occurred in one patient (2.5%). No delayed aneurysm rupture, subarachnoid or intraparenchymal hemorrhage, or ischemic complications occurred and there were no deaths. Conclusions: Endovascular treatment with the p64 Flow Modulation Device is a safe treatment for unruptured cerebral aneurysms, resulting in a high rate of occlusion. As with other flow diverter devices, we recommend this treatment mainly for large-necked aneurysms of the internal carotid artery siphon. However, endovascular treatment with the p64 device should also be encouraged in difficult cases such as aneurysms of the posterior circulation and beyond the circle of Willis.